The Role of Change Management in Increasing the Competitiveness of PT. Denta Sumut's Ceiling Sales - Mulyani, Sri; Astuti, Citra; Aulia, Muhammad Rizki (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyze the role of change management in increasing the competitiveness of ceiling sales at PT. Denta Sumut. Amidst the increasingly competitive building materials industry in North Sumatra, PT. Denta Sumut undertook an organizational transformation to address sales stagnation. This study employed a descriptive qualitative approach, with data collection techniques including participant observation, in-depth interviews with management and sales staff, and a documentary study of company reports. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using the Miles and Huberman model.The results indicate that the implementation of change management at PT. Denta Sumut played a significant role through three main aspects. First, the transformation of the work culture from a transactional to a relational mindset improved the quality of customer relationships. Second, the digitization of the inventory monitoring and sales reporting systems successfully created operational efficiencies and accelerated lead times. Third, a product differentiation strategy that was more adaptive to local interior design trends expanded the company's market share. Overall, the integrated change management of Human Resources (HR) and information technology has strengthened PT. Denta Sumut's bargaining position and created a sustainable competitive advantage